The Role Of Radio In Problem Solving On The Perceptual Situation To The Insufficient Information Delivery For Malaysia's Agricultural Extension Services - Idris Ismail; Rosidayu Sabran; Mohd Yahya Mohamed Ariffin (UKM, 2024)
Jurnal Komunikasi: Malaysian Journal of Communication Jilid 35(2) 2019: 331-345